The Paradox of Downstream Mining Industry Development in Indonesia: Analysis and Challenges - Atik Krustiyati; Gita Venolita Valentina Gea (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Development of downstream on the mining industry has been encouraged by the government of Indonesia these past years. With the increasing demand for nickel ore, the government focused on implementing downstream in this sector. Establishing an export ban and domestic processing requirement on nickel ore caused the EU to challenge Indonesia before the DSB WTO. In its report to the Panel, it was concluded that Indonesia had violated the provisions of GATT 1994. While it is understandable that Indonesia has absolute sovereignty over its natural resources, it is also bounded to international organisations and regulations, for it has expressed its consent. This paper aims to examine the analysis by the Panel on what caused Indonesia to decide as the losing party and how Indonesia would implement the development downstream in the middle of its sovereignty and obligations on an international level. Through a juridical normative method, it is concluded that Indonesia had failed to comply with the provisions of GATT 1994 that obliged it. It does not mean it has no sovereignty towards its natural resources, for it has agreed to be bound by the provisions. In order to exercise downstream development, it is recommended that Indonesia create national policies or regulations related to adhering to the provisions of the WTO. A cautious approach to governing the downstream may prevent potentially damaging disputes.